„Trening orientacji i zarządzania czasem” w toku czynności dnia codziennego z osobami z niepełnosprawnością intelektualną w stopniu umiarkowanym - Hinc-Wirkus, Magdalena (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
A human is a social being, instinctively aspiring to become fully involved with the society. According to the statistics, however, one in ten Polish people is forced to overcome various problems in order to be active in the society. What are the main problems for a person with intellectual disability and their career? One of the main barriers for persons with intellectual disability, are the difficulties with the perception of the time; comprehending the very idea of the time flow and learning to use the watch or the calendar. A simple and cost-effective way to develop these skills is the training in time comprehension (‘The Time Workshop’), which is the subject of this article.